Madeira caída como oportunidade para o manejo florestal comunitário em unidades de conservação no Amazonas - Rocha, Janaína de Almeida (Instituto Nacional de Pesquisas da Amazônia - INPA, 2010)
Protected areas are the central piliar of the strategies for conservation of biodiversity on the planet. However, millions of people woridwide depend directiy on forest resources for subsistence, especially dwellers on legaiiy protected areas. The use of natural resources In generating income for communities is common in tropical countries. In the Amazon, wood product is widely used for subsistence and income generation. However, timber harvesting in the region is predatory because it concentrates wealth and causes deforestation. In addition, less than half the roundwood taken from the forest is transformed into forest products, which generates large amounts of waste. The human communities of protected areas in Brazil could play an important role in protecting their territories. In order to contribute for the development of the culture of forest management in protected areas, the purpose of this study is to verify the feasibility of using falien tree as raw material for making small wooden products. The foilowing studies were carried out: falien tree volume estimates, economical feasibility based on benefit-cost analysis of small wooden products, and chemical analyses for 20 different wood species that could be used for small wooden products. The average volume of falien timber in the four sites studied ranged between 6.71 ± 3.12 and 9.19 ± 2.41 m^ha"'' (Cl 95%), which is feasible for management in a community context or even a furniture industry. The plan is the introduction of marquetry techniques for small wooden products, perhaps for furniture as well. Ali tree species chemically analyzed have shown leveis of extractives are near those expressed in the literature for the same species. About the occurrence of potentially toxic compounds, there was absence of cyanogenic heterosides in ali samples analyzed. Some species have potentially toxic compounds that should be better studied for the appiication of these species in kitchen utensils or toys. This study it was found out that the management of falien trees is feasible, and could be an important flow-in income for dwellers at conservation unit in the Brazilian Amazon. The information generated by this work will aggregate technology and possibilities for the full use of the stem, improving the management of tropical timber without cutting trees.
Keywords: Madeira caída; Manejo florestal